Ocular findings in leprosy patients in an institution in Nepal (Khokana). Issue 4 (April 1981) - Malla, O K; Brandt, F; Anten, J G
Abstract : A total of 466 leprosy patients in Nepal, some advanced cases, were surveyed for ocular lesions. 74.2% were found with ocular features, and 12.7% of the eyes were blind. The patients were classified in tuberculoid, borderline-borderline, and lepromatous groups. Lepromatous leprosy is responsible for major ocular complications and blindness.